Lanceola felina Bovallius 1885 ... - Thacker, Dimple; Patel, Krupal; Myers, Alan; Guerra-García, José M.; Zeidler, Wolfgang; Trivedi, Jigneshkumar (Zenodo, 2023)
112. Lanceola felina Bovallius, 1885 Type locality: Tristan da Cunha, South Atlantic Ocean. Distribution. Synonyms: Lanceola curticeps Bovallius, 1885; Lanceola felina var. longipes Woltereck, 1909. World: Tristan da Cunha (Bovallius 1885), India (Zeidler 2009). India: Andaman and Nicobar Islands Ecoregion: Andaman and Nicobar Islands (Zeidler 2009). ... : Published as part of Thacker, Dimple, Patel, Krupal, Myers, Alan, Guerra-García, José M., Zeidler, Wolfgang & Trivedi, Jigneshkumar, 2023, Annotated Checklist of Marine Amphipods (Crustacea: Amphipoda) of India, pp. 1-90 in Zootaxa 5340 (1) on page 48, DOI: 10.11646/zootaxa.5340.1.1, http://zenodo.org/record/8324090 ...